If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 2) = 6x + 10x + 2 Reorder the terms: -4(2 + x) = 6x + 10x + 2 (2 * -4 + x * -4) = 6x + 10x + 2 (-8 + -4x) = 6x + 10x + 2 Reorder the terms: -8 + -4x = 2 + 6x + 10x Combine like terms: 6x + 10x = 16x -8 + -4x = 2 + 16x Solving -8 + -4x = 2 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -8 + -4x + -16x = 2 + 16x + -16x Combine like terms: -4x + -16x = -20x -8 + -20x = 2 + 16x + -16x Combine like terms: 16x + -16x = 0 -8 + -20x = 2 + 0 -8 + -20x = 2 Add '8' to each side of the equation. -8 + 8 + -20x = 2 + 8 Combine like terms: -8 + 8 = 0 0 + -20x = 2 + 8 -20x = 2 + 8 Combine like terms: 2 + 8 = 10 -20x = 10 Divide each side by '-20'. x = -0.5 Simplifying x = -0.5
| (x+5)2-(x+5)(x-5)= | | -5r-2r=-15-8r+3+7 | | 4x-5=4x+9 | | -3w+8(w-4)=-2 | | 7-2b=19 | | 75=10x-5 | | 1+b=-18-4 | | 27+3x=111 | | -13m+7m=19-73 | | 5x+11=12x-10 | | 10x-2-6x=3y-2+y | | 3x+15+9x+21=180 | | -11x-20=10+40 | | 6y+12=3t+14 | | 6(v+4)-4v=4 | | 14s+2.00=20s+1.50 | | 15Z-32=13 | | -9=-5+t | | x=3+2i | | 14s+2=20s+150 | | -9=5+t | | 8x-7=6x+23 | | 2(x-3)=2*x | | 2w-6w=56 | | 5x+6+6x+5=50 | | -3(h+5)+2=4(h+6) | | 4a-4a^2=0 | | -88-12X=7-2x-6 | | R+20=50 | | -x^4-2x^2+1=0 | | 11+4p=4+3p | | 5-9n+5n=27-82 |